Cauchy problem for doubly degenerate parabolic equation with gradient source. (January 2015) - Shang, Haifeng; Cheng, Junxiang
Abstract: We consider the Cauchy problem for a doubly degenerate parabolic equation with a source term depending solely on the gradient. A major result of this paper is to establish the local existence of solutions for this equation under optimal stipulated assumptions on the initial data.